How do We Use Our Words in the World where Lies are Rampant? From Augustine's Argument on Lying - Sato, Makiko (Editorial Uniagustiniana, 2019)
This chapter examines how Augustine inspires us to live at peace with our world where lies are rampant. We see many cases of lies having power and truths being ignored in politics, media and other situations. In some of his works, Augustine expresses the idea that every kind of lie is a sin. His strict ban on lying has often be seen as abstract and unrealistic, because we consider lying to be sometimes useful and helpful, while regretting the situations in which lies are rampant. In the first part of this chapter, the author points out how Augustine's ban on lying has a certain kind of permissibility and that he leads us to focus on whether a liar loves truth/God or not. Augustine sets a certain criterion for the sin of lying in one's mindset in terms of loving truth/God or not. The second part of this chapter will show that Augustine thinks a person who tells a lie willingly does not love truth, and as a result she or he will lose true happiness. Augustine thinks that the liar's mindset, which willingly tells a lie, will cause great evils as well. This mindset also loses the healing of Christ. In the last part of the chapter, the author argues that Augustine finds utility in words that prevent our being liars and enable the enjoyment of the unity of truth and God. According to Augustine, we can speak truth when we speak what we heard from the truth. The truth is the Word, Christ. Augustine's argument on lying deeply connects with his Christology and that enables him to suggest how to use our words in the world where lies are rampant.